L'«apprendimento insegnato»: valutazione per l'apprendimento vs. valutazione dell'apprendimento - Concetta La Rocca; Rosa Capobianco (LED Edizioni Universitarie, 2016)
In this paper we present the procedures and the results of an observational study carried out in the first half of AS 2015/2016 into two 3th classes of the Professional Institute of Palestrina (RM) and carried out as part of the PRIN Research (2013-2016). In one of the classes, considered as experimental class, the model of Didactic Modular Integrated Strategy (in Italian - SDiMI) was applied, in the other one, considered as the control class, the traditional teaching was continued to use. The SDiMI model, to which the teachers of the experimental class were formed, respect to the different elements that compose it, provides the application of the assessment as training function. In the time period of the teaching/evaluation intervention observation, two standardized questionnaires (in input and output), about the type of assessment used in class (Alkharusi, 2015; in Italian translation) were administered to teachers and students. Assessment tests (objective and semi-structured tests) were administered to the students. The analysis of the data showed a marked improvement in the experimental class, compared to the control class, of both the assessment activities used in training function, detected through the questionnaires, and the outcome of the students' performance, especially in the reading tests and in the semistructured logical-mathematical test.